Evaluation of Failure in Single-Piece Implant Systems: A One-Year Follow-Up Study - Hymasree Betha; Sagar Gopalakrishna; Arvind K Pal; Harisha Dewan; V H Dhanya; Banavath S. S R. Sameer Kumar Naik; Rahul V C. Tiwari (Wolters Kluwer Medknow Publications, 2024)
Objective: This study's goal was to assess the failure rate and peri-implant complications of single-piece implant systems over the course of a one-year follow-up. Materials and Methods: Patient records were examined retrospectively. 150 single-piece dental implants were analyzed. Clinical results, implant features, and demographic information were gathered. Implant failure, which is characterized as the total loss of osseointegration, served as the key outcome indicator. Patient satisfaction and peri-implant problems were secondary outcomes. Data analysis employed descriptive statistics. Results: During the one-year follow-up period, the failure rate for single-piece implant systems was 6.7%. The two main factors leading to implant failure were found to be poor osseointegration (60%) and biomechanical overload (40%). 20% of the cases had peri-implant problems, such as peri-implantitis. 85% of the panelists felt that single-piece implants had satisfied their patients. Conclusion: A 6.7% failure rate in single-piece implant systems was seen in this one-year follow-up investigation. The major causes of implant failure were found to be poor osseointegration and biomechanical loading. In 20% of the cases, peri-implant problems such as peri-implantitis, were noted. There was great patient satisfaction. These results highlight the significance of regulating occlusal forces, optimizing osseointegration, and applying preventive measures to ensure the long-term viability of single-piece implant systems.